Response to Imported Case of Marburg Hemorrhagic Fever, the Netherlands - Timen, Aura (Centers for Disease Control and Prevention, 2009)
On July 10, 2008, Marburg hemorrhagic fever was confirmed in a Dutch patient who had vacationed recently in Uganda. Exposure most likely occurred in the Python Cave (Maramagambo Forest), which harbors bat species that elsewhere in Africa have been found positive for Marburg virus. A multidisciplinary response team was convened to perform a structured risk assessment, perform risk classification of contacts, issue guidelines for follow-up, provide information, and monitor the crisis response. In total, 130 contacts were identified (66 classified as high risk and 64 as low risk) and monitored for 21 days after their last possible exposure. The case raised questions specific to international travel, postexposure prophylaxis for Marburg virus, and laboratory testing of contacts with fever. We present lessons learned and results of the follow-up serosurvey of contacts and focus on factors that prevented overreaction during an event with a high public health impact.